Karakteristik Eksekutif, Intensitas Modal dan Faktor Lain Terhadap Agresivitas Pajak - Baihaqi, Faza Naufal Rifanda; Sutrisno, Paulina (Forum Kerjasama Pendidikan Tinggi, 2024)
The aim of this research is to obtain empirical evidence regarding the influence of executive characteristics, capital intensity, company size, institutional ownership, independent commissioners and audit committees on tax aggressiveness. This research is quantitative research, using secondary data obtained from the financial reports of public companies listed on the Indonesia Stock Exchange. The sample for this research is manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. The sample was selected using a purposive sampling method. The research hypothesis was tested with fixed effect panel data with the help of STATA software. The results of this research show that capital intensity has a negative effect on tax aggressiveness, because companies with high capital intensity will have high depreciation expenses which can reduce the company's tax burden. Meanwhile, executive characteristics, company size, institutional ownership, independent board of commissioners, audit committee have no effect on tax aggressiveness.